Towards pair production in the non-perturbative regime. (12th October 2021) - Salgado, F C; Grafenstein, K; Golub, A; Döpp, A; Eckey, A; Hollatz, D; Müller, C; Seidel, A; Seipt, D; Karsch, S; Zepf, M
Abstract: The interaction of light with the quantum-vacuum is predicted to give rise to some of the most fundamental and exotic processes in modern physics, which remain untested in the laboratory to date. Electron–positron pair production from a pure vacuum target, which has yet to be observed experimentally, is possibly the most iconic. The advent of ultra-intense lasers and laser accelerated GeV electron beams provide an ideal platform for the experimental realisation. Collisions of high energy γ -ray photons derived from the GeV electrons and intense laser fields result in detectable pair production rates at field strengths that approach and exceed the Schwinger limit in the centre-of-momentum frame. A detailed experiment has been designed to be implemented at the ATLAS laser at the centre of advanced laser applications. We show full calculations of the expected backgrounds and beam parameters which suggest that single pair events can be reliably generated and detected.